Evidence for a Growth-Stabilizing Regulatory Feedback Mechanism between Myc and Yorkie, the Drosophila Homolog of Yap. - Neto-Silva, R.M.; de Beco, S.; Johnston, L.A. (Developmental Cell, 2010)
An understanding of how animal size is controlled requires knowledge of how positive and negative growth regulatory signals are balanced and integrated within cells. Here we demonstrate that the activities of the conserved growth-promoting transcription factor Myc and the tumor-suppressing Hippo pathway are codependent during growth of Drosophila imaginal discs. We find that Yorkie (Yki), the Drosophila homolog of the Hippo pathway transducer, Yap, regulates the transcription of Myc, and that Myc functions as a critical cellular growth effector of the pathway. We demonstrate that in turn, Myc regulates the expression of Yki as a function of its own cellular level, such that high levels of Myc repress Yki expression through both transcriptional and posttranscriptional mechanisms. We propose that the codependent regulatory relationship functionally coordinates the cellular activities of Yki and Myc and provides a mechanism of growth control that regulates organ size and has broad implications for cancer.